Penguatan Branding Desa Wisata Sawah Terasiring Melalui Strategi Promosi Digital Dan Pemasaran Berkelanjutan - Nora Listantia; Muhammad Diaz Naufal Akhdiyat; Arif Rahman; Bening Sagita Lestari; Riska Ageng Pangestu; Zaura Fatilla; Risa Nadia Astuti; Putri Handayani; Khairul Wajdi; Beni Nasriadi; Fitri Aliyah; Karoluslina; Sartika Hijriati; M. Gunawan Supiarmo (Universitas Mataram, 2026)
Thematic Community Service Program (Kuliah Kerja Nyata/KKN) is a form of community engagement that plays a strategic role in supporting village development, particularly in the tourism sector based on local potential. This community service activity was carried out using a participatory approach, involving the community actively from the stages of observation, planning, implementation, to evaluation of the activities. The work programs implemented included the construction of a photo spot stage, the installation of TPQ signboards, teaching Qur’an recitation at the TPQ, community clean-up activities, and weekly exercise sessions with village children. The results of the activities showed that the construction of the photo spot stage was able to strengthen the visual identity of Mareje Village as a nature- and agriculture-based tourism village, as well as improve the effectiveness of digital promotion through social media platforms such as Instagram and TikTok. In addition, the social and educational programs had a positive impact on strengthening TPQ institutions, increasing children’s participation in religious and sports activities, and raising public awareness of the importance of environmental cleanliness and social collaboration. Overall, this KKN program contributed to encouraging sustainable village tourism development in social, economic, and environmental aspects.